2011
DOI: 10.1590/s1516-35982011000600002
|View full text |Cite
|
Sign up to set email alerts
|

Growth of white clover seedlings treated with aqueous extracts of leaf and root of tough lovegrass

Abstract: -This study was carried out to investigate the effect of extracts of leaf and roots of tough lovegrass (Eragrostis plana) on seedling growth of white clover (Trifolium repens), in two experiments. The first experiment was conducted as a pilot test, in which two concentrations (30 and 60%) of leaf aqueous extract were tested. In Experiment II, source (leaf/root) and concentration (5 and 10%) of the extracts were combined. Distilled water was used as control in both trials. Fifty seedlings at 7 days of age were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 6 publications
4
12
0
2
Order By: Relevance
“…At the vegetative stage, probably because the time between the applications of N and the harvest was the shortest, there was no difference 5 among doses. In the tough lovegrass that was not fertilized with N, Alfaya et al (2002) The allelopathic effect of the aqueous extracts on lettuce was visually observed (Figure 3) and quantified according to the germinability and the GSI (Table 2), in accordance with other authors who evaluated the allelopathic potential of the tough lovegrass (Ferreira et al, 2008;Favaretto et al, 2011). The allelopathic symptoms, in a greater or a lesser degree and depending of the extract, included necrosis, shortening and winding of the root apex (Figure 3), which is commonly reported in bioassays of this type (Souza Filho et al, 1997).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…At the vegetative stage, probably because the time between the applications of N and the harvest was the shortest, there was no difference 5 among doses. In the tough lovegrass that was not fertilized with N, Alfaya et al (2002) The allelopathic effect of the aqueous extracts on lettuce was visually observed (Figure 3) and quantified according to the germinability and the GSI (Table 2), in accordance with other authors who evaluated the allelopathic potential of the tough lovegrass (Ferreira et al, 2008;Favaretto et al, 2011). The allelopathic symptoms, in a greater or a lesser degree and depending of the extract, included necrosis, shortening and winding of the root apex (Figure 3), which is commonly reported in bioassays of this type (Souza Filho et al, 1997).…”
Section: Resultssupporting
confidence: 84%
“…The allelopathic symptoms, in a greater or a lesser degree and depending of the extract, included necrosis, shortening and winding of the root apex (Figure 3), which is commonly reported in bioassays of this type (Souza Filho et al, 1997). These symptoms were observed in white clover seedlings (Trifolium repens, Fabaceae) that were subjected to leaf and root extracts of the tough lovegrass (Favaretto et al, 2011).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This alien African grass is the most abundant and aggressive invasive plant in the Pampa Biome, responsible for causing widespread economic impacts on livestock by modifying the structure of plant communities and by affecting ecological balances. The heterotoxicity of tough lovegrass was been observed in bioassays of seed germination with white clover (Trifolium repens), Italian ryegrass (Lolium multiflorum), African bristlegrass (Setaria sphacelata), and bahiagrass (Paspalum notatum) (Coelho, 1986;Ferreira et al, 2008;Favaretto et al, 2011). However, it was assumed that tough lovegrass may also display autotoxicity, because in the field, the clumps are separated from each other by empty spaces with bare soil radius of 5-10 cm (Coelho, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Its occurrence is common in overgrazed and excessively burned pasture (Brink, 2006), which amplifies its establishment and persistence, reducing the presence of species with better nutritive value. The species also presents active allelopathic mechanisms, inhibiting the germination and seedling growth of others species (Coelho, 1986;Favaretto et al, 2011). Medeiros & Focht (2007) suggested the possibility of restoring the natural pastures contaminated by this grass by manipulating grazing pressure of less selective herbivores, rotational grazing, deferment, protein/energetic supplementation, and strategic mowing to avoid seed production.…”
Section: Introductionmentioning
confidence: 99%